The Effect Of Digital Leadership On Digital Skills With Employee Dynamic Capabilities As A Mediating Variable In MSMES In West Sumatra (Management Studies and Entrepreneurship Journal (MSEJ), 2025)
Digitalization requires micro, small and medium enterprises (MSMEs) to increase leadership capacity and employee competence in the use of technology. This study examines the effect of digital leadership on employee digital skills with employee dynamic capabilities as a mediating variable in MSMEs in West Sumatra Province. The problem raised is that the digital skills of employees are not yet optimal in supporting technological adaptation, and the role of leadership has not fully encouraged employees' innovative and adaptive abilities. This study aims to measure the level of digital leadership can affect digital skills, either directly or indirectly through dynamic capabilities. The method used is a quantitative approach with a survey technique using a questionnaire. The number of respondents was 190 MSME employees selected using purposive sampling technique. Data were analyzed using the Structural Equation Modeling (SEM) method based on Partial Least Squares (PLS). The results showed that digital leadership has a significant effect on employee digital skills. In addition, employees' dynamic capabilities were shown to significantly mediate the relationship. The findings indicate that the role of digital leaders is able to guide, facilitate, and inspire. By having an important contribution in shaping employees who are adaptive, innovative, and skilled in facing the digital era.